Pengaruh Kesadaran Wajib Pajak, Sikap Wajib Pajak Atas Pelaksanaan Sanksi Denda Dan Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Bumi Dan Bangunan (Studi Kasus Wajib Pajak Bumi Dan Bangunan Di Kabupaten Bantul) - Suyanto, Suyanto; Purwanti, Purwanti (Akmenika: Jurnal Akuntansi dan Manajemen, 2016)
The purpose of this study was to examine the influence awareness of the taxpayer, the taxpayer stance on the implementation of financial penalties, and quality of service tax authorities on tax compliance and building earth. This research was conducted at the Department of Revenue, Finance and Asset Management of Bantul through 110 respondents. The data analysis technique used is multiple linear regression technique which consists of one dependent variable is tax compliance, and three independent variables taxpayer awareness, the attitude of the taxpayer on the implementation of financial penalties, and quality of service tax authorities. Based on the analysis performed, it is known that the awareness of the taxpayer, the taxpayer stance on the implementation of financial penalties, and quality of service tax authorities simultaneously and partially on tax compliance and building earth. The predictive ability of the independent variable on the dependent variable showed independent variables are able to explain the dependent variable variation of 33.8% and 66.2% explained by other variables.